Synergistic Effects of Salt Concentration and Working Temperature towards Dendrite-Free Lithium Deposition - Panlong Li; Chao Li; Yang Yang; Chanyuan Zhang; Renhe Wang; Yao Liu; Yonggang Wang; Jiayan Luo; Xiaoli Dong; Yongyao Xia (Research, 2019)
The lithium- (Li-) metal anode is crucial for developing high-energy-density batteries, while its dendritic growth and the low charge/discharge Coulombic efficiency in organic electrolytes hinder its practical application. Herein, we employed an in situ optical microscope to investigate the effect of the electrolyte concentration and the working temperature on the Li-plating/-stripping process. It is found that a higher concentration electrolyte can suppress its side reaction to improve the charge/discharge Coulombic efficiency, and a higher temperature can help lithium plate/strip uniformly with less lithium dendritic growth. An average Coulombic efficiency was obtained as high as 99.2% for over 150 cycles with a fixed plating capacity of 2 mAh cm-2 on copper foil in a 3 mol/kg ether-based electrolyte under 60°C, which provides an efficient and facile strategy for developing high-performance Li-metal batteries.